From surface to caves: new species of Diploexochus Brandt, 1833 (Oniscidea, Armadillidae) from Colombia, with the description of the first troglobitic species - Ricardo Borja-Arrieta; Carlos Mario López-Orozco; Yesenia M. Carpio-Díaz; Miguel Gutierrez-Estrada; Ivanklin Soares Campos-Filho; Gabriel R. Navas-S.; Maria Elina Bichuette (ZooKeys)
Two new species of Diploexochus are described, Diploexochus cacique sp. nov. from Cerro Bañaderos in Hatonuevo, La Guajira, and Diploexochus troglobius sp. nov. from Roca Madre Cave, Toluviejo, Sucre, both from the Tropical Dry Forest (TDF) areas of the Colombian Caribbean. The latter represent the first troglobitic species of the genus. Moreover, based on specimens from Sierra Nevada de Santa Marta, Magdalena (type locality), Venezillo brevispinis is placed into Diploexochus and an identification key for all species of the genus is given. The present work describes the first troglobitic species of the genus, and expand the knowledge of its distribution in northern South America.